Perancangan Aplikasi Sistem Informasi Stok Stiker di Gudang Ban PCR Berbasis VB.NET - Riza Amartya Pradana; Rizki Azis Prayuda; Muhammad Ridwan Arif Cahyono (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
With the rapid development of information, warehouses need to manage their daily activities. need proper management of production receipts, warehouse storage, and delivery according to customer delivery schedule. The three processes use check sheets carried out by workers in the area. The use of check sheets resulted in workers inputting very large number of sticker data. then the need for an information system on the stock sticker contained in the PCR tire warehouse. The information system uses the Unified Modeling Language approach or can be called UML so that it is easier to understand. The information system is arranged using a desktop application to monitor sticker stock in the field. The method used in designing the application is the waterfall method, the waterfall method contains planning, modeling, design or development, and implementation. The results obtained from this study are an information system that presents data in the form of the actual number of stickers in the field so that the number of sticker items can be monitored.